Avaliação dos efeitos da pandemia de Covid-19 sobre a evasão estudantil nos cursos superiores de tecnologia do IFSP São Carlos - Mendes, Ricardo Pertile Frota Teixeira (2022)
This work is about education, particularly, the phenomenon of student dropout, a common and recurrent problem in educational institutions in general. Studies indicate that the students who start, but do not finish their courses are related to social, academic and economic loss. In the public sector, they correspond to public resources invested without the expected return to society. The research target of the work is the Federal Institute of Education, Science and Technology of São Paulo, São Carlos campus, covering the period that marks the beginning of the Covid-19 pandemic in Brazil, from mid-March 2020 until December de 2021. The main objective is to understand the strategies to combat student dropout in higher technology courses on campus occurred during the Covid-19 pandemic. In order to evaluate the phenomenon from a chronological perspective, it was decided to break down the main objective into three specific objectives: 1. To verify the institutional response to the pandemic. 2. Evaluate the phenomena of dropout and student retention and the institutional response during the pandemic and 3. Compare dropout indicators before and after the pandemic. The methodological structure includes a bibliographic review, document analysis and participant observation, conducted through semi-structured interviews with representative agents, employees of the institution who work directly and behind the scenes of teaching, including administrative technicians who provide support as facilitators and teachers, the leading characters of the emergency remote teaching system. The evaluation of the Covid-19 institutional contingency plan by the interviewees was positive, contrasting with the common perception of the intensification of dropout phenomenon in the period. Despite the gap between the onset of the pandemic and institutional actions to combat it, good indicators were found for evasion, suggesting that the positive results obtained may be artificial, being biased by the institutional policy.